Mediation as an alternative mode of resolving family disputes in Malaysia / Su'aida Safei - Su'aida, Safei (2005)
This dissertation attempts to explore the possibilities of introducing mediation to settle family disputes, as an alternative to litigation in the Malaysian High Court. Family matters are seen as sensitive that deserve to be treated in confidence and in a less formal manner. The special features of mediation are of paramount importance to disputes of family nature, namely; confidentiality, informality and flexibility of its processes. Delay in disposing civil cases including family cases should not be tolerated. Prolonged litigation may also lead to high expenses incurred by parties in family disputes. Most importantly, it is saddening to see matters concerning private lives of people being dealt openly in court that may cause embarrassment to the family members as a whole. Since Malaysia has a dual family system for the non-Muslims in the High Court and for Muslims in the Shariah Court, mediation or known as sulh as practised in the Selangor Shariah Courts will be studied. Mediation as conducted by the Bar Council's Malaysian Mediation Centre will also be compared. The study will also include the practices of family mediations in Singapore and Australia. It is the objective of this dissertation to analyse and scrutinise the practice of mediations for family disputes in the above jurisdictions to examine the possibility of incorporating mediation as part of a pre-trial process before any family law cases are heard in the Malaysian High Court. A comparative study of mediation in various jurisdictions, as stated earlier, will identify a suitable model for the Malaysian High Court to adopt in settling its family law cases. This dissertation will make recommendations and propose reforms, where necessary.